Kajian Tentang Remunerasi Terhadap Kinerja Pegawai Dengan Kepuasan Kerja Sebagai Variabel Mediasi Di Politeknik Negeri Malang - Rusli, Rusli (Arthavidya Jurnal Ilmiah Ekonomi, 2019)
Abstract: Remuneration is the implementation of Minister of Research,Technology and Higher Education Regulation Number 31 Year 2016 andMalang State Polytechnic Director Regulation Number 262 2016 which isgiven to employees with the status of Civil Servants. The purpose of this studywas to examine and analyze the effect of remuneration on job satisfaction,remuneration on employee performance, job satisfaction on performance andthe effect of remuneration on employee performance at the State Polytechnicof Malang through employee job satisfaction at the State Polytechnic ofMalang. This study uses a quantitative approach by emphasizing its analysisof numerical data that is processed by statistical methods in the context ofsubmitting hypotheses. The sample used was 75 employee respondents at thecentral office with the status of Civil Servants. The results showed thatremuneration had a significant effect on job satisfaction, remuneration had asignificant effect on employee performance, job satisfaction had a significanteffect on employee performance and remuneration had a significant effect onemployee performance mediated by variable job satisfaction.Keywords: Remuneration, job satisfaction, employee performance